Genetic diversity and antifungal activity of native Pseudomonas isolated from maize plants grown in a central region of Argentina - Cordero Gabrielli, Paula Verónica (2012)
Pseudomonas strains producing antimicrobial secondary metabolites play an important role in the biocontrol of phytopathogenic fungi. In this study, native Pseudomonas spp. isolates were obtained from the rhizosphere, endorhizosphere and bulk soil of maize fields in Córdoba (Argentina) during both the vegetative and reproductive stages of plant growth. However, the diversity based on repetitive-element PCR (rep-PCR) and amplified ribosomal DNA restriction analysis (ARDRA) fingerprinting was not associated with the stage of plant growth. Moreover, the antagonistic activity of the native isolates against phytopathogenic fungi was evaluated in vitro. Several strains inhibited members of the genera Fusarium, Sclerotinia or Sclerotium and this antagonism was related to their ability to produce secondary metabolites. A phylogenetic analysis based on rpoB or 16S rRNA gene sequences confirmed that the isolates DGR22, MGR4 and MGR39 with high biocontrol potential belonged to the genus Pseudomonas. Some native strains of Pseudomonas were also able to synthesise indole acetic acid and to solubilise phosphate, thus possessing potential plant growth-promoting (PGPR) traits, in addition to their antifungal activity. It was possible to establish a relationship between PGPR or biocontrol activity and the phylogeny of the strains. The study allowed the creation of a local collection of indigenous Pseudomonas which could be applied in agriculture to minimise the utilisation of chemical pesticides and fertilisers.